2021
DOI: 10.1093/advances/nmaa110
|View full text |Cite
|
Sign up to set email alerts
|

Association of Consumption of Sugar-Sweetened Beverages or Artificially Sweetened Beverages with Mortality: A Systematic Review and Dose–Response Meta-Analysis of Prospective Cohort Studies

Abstract: Sugar-sweetened beverage (SSB) and artificially sweetened beverage (ASB) intakes have been reported to be associated with mortality; however, conclusions have been inconsistent. This review synthesized the evidence on the associations of SSB and ASB intakes with mortality from all causes, cardiovascular disease (CVD), and cancer among all populations (including general, diseased, or occupational populations, etc.). PubMed, EMBASE, Web of Science, Cochrane Library, ProQuest, ClinicalTrials.gov, and the Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…Positive associations between SSB and all-cause mortality risk have also been reported in recent meta-analyses of cohort studies [ 4 , 7 , 8 , 23 ], where particularly the largest studies support our findings [ 11 , 12 , 24 27 ]. A pooled prospective analysis of the Nurses’ Health Study and Health Professional Follow-up Study [ 12 ] yielded a 7% higher mortality risk for each additional serving/day.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Positive associations between SSB and all-cause mortality risk have also been reported in recent meta-analyses of cohort studies [ 4 , 7 , 8 , 23 ], where particularly the largest studies support our findings [ 11 , 12 , 24 27 ]. A pooled prospective analysis of the Nurses’ Health Study and Health Professional Follow-up Study [ 12 ] yielded a 7% higher mortality risk for each additional serving/day.…”
Section: Discussionsupporting
confidence: 92%
“…Yet, evidence on the impact of sugar-sweetened beverages (SSB) and low/no-calorie beverages (LNCB) on mortality risk remains scarce and inconclusive. Recent dose–response meta-analyses showed significant positive associations between SSB and LNCB consumption and all-cause mortality risk [ 4 , 7 , 8 ], but also showed moderate to high heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies showed us that consumption of SSB is associated with an increased risk for central obesity and increased visceral fat [59][60][61][62] , MS [59,63] , dyslipidemia [64] , T2DM [63,[65][66][67] , cardiovascular diseases [63,68] , and mortality [69] .…”
Section: Fructose and Sugar-sweetened Beveragesmentioning
confidence: 99%
“…Increasing fructose and SSB consumption, particularly among adolescents and young adults, is troublesome because substantial evidence links consumption to various health outcomes, including obesity, type 2 diabetes, cardiovascular disease, some cancers, all-cause mortality, and now early-onset high-risk adenoma. 10,11,21 Future research should explore the mechanisms by which excess fructose drives colorectal carcinogenesis, as well as the effects of SSBs' individual components, such as food coloring (eg, caramel). Although we are still a long way from connecting the dots from fructose to early-onset CRC, clinicians should continue to support public health policies discouraging or reducing consumption of simple sugars and SSBs in adolescents, for whom exposure might have lifelong consequences.…”
mentioning
confidence: 99%